(untitled) (Samsad Journal संसद जर्नल, 2024)
The paper discusses the concept of an eminent domain with special reference to land acquisition and the significance of the compensation payment to the concerned person. Each individual has rights regardless of their background, however, not all rights are absolute in nature. The government, in its official capacity, can acquire or withhold certain rights, such as the right to property, through the doctrine of eminent domain. Thus, eminent domain is a power of the government to acquire private property for public use, as long as it serves a public purpose. This power, inherent to sovereignty, typically doesn’t need constitutional recognition. However, the government must fulfill due diligence and prerequisites before encroaching upon individual property rights. Eminent domain reads for an adequate compensation as a crucial element for its application. The paper aims to explore the theoretical aspects of eminent domain, referencing to the significance of compensation payment and public benefit as justifiable grounds to invoke the power of eminent domain. It analyzes the conditions under which property can be lawfully expropriated through eminent domain and the grounds for justifiable acquisition. Additionally, it delves into how compensation is determined and provided to ensure it is fair and reasonable.